Quality of life of patients with heart failure: a quantitative study. - Liana Amorim Corrêa; Iraci dos Santos; Ricardo Mourilhe Rocha; Bernado Rangel Tura; Denilson Campos de Albuquerque (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Introduction: Heart failure is a syndrome that affect 10 individuals in 1000 after 65 years old in the United States of America. It is considered the final way of all cardiologic diseases and is estimated to be the first cause of death in the world around 2025. Some studies point to poor quality of life in clients with this syndrome. Objective: This study sought to verify the contribution of nursing care based on sensitive listening contributes to improvement quality of life in heart failures clients. Method: It was a prospective quasi-experimental study that used the Minnesota questionnaire to evaluate the quality of life of heart failure  clients. Results: We observed a significant improvement of quality of life after 4 months of nursing care follow-up (20.8±18.1 vs. 32.9± 20.1 p <0.001) corroborating this finding to other found in previous studies. Conclusion: We concluded that the implementation of a technology that focuses the subject during nursing care has been shown to be effective and  improving health and quality of life of patients with heart failure.